Integrasi Kurikulum Antikorupsi: Peluang dan Tantangan: Integration of Anti-Corruption Curriculum in FKM UI: Opportunities and Challenges - Ayuningtyas, Dumilah (Komisi Pemberantasan Korupsi, 2020)
Based on data from Indonesia Corruption Watch (ICW) in 2018, health sector corruption cases caused state losses of Rp 3.7 billion. This study aims to measure corruption knowledge and the urgency of anti-corruption education in Faculty of Public Health University of Indonesia (FKM UI). A quick survey was conducted on 198 students, in addition to interviews with experts. The results of the study showed that knowledge about corruption was still low at 64.64 %. There is full support of students (100%) of the importance of anti-corruption education and also from all experts. The support of integration of anti-corruption education with curriculum is delivered by 92, 4% respondent. The discussion, case studies and role-play became the most proposed on learning methods. The low knowledge of anti-corruption reinforces the urgency of anti-corruption education integrated with curriculum. Campus has the opportunity with the availability of expertise and support of infrastructure, in addition to the challenges of adjusting the curriculum.